2012
DOI: 10.1037/a0025861
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of academic English proficiency outcomes for adolescent English language learners in the United States.

Abstract: The recent availability of nationally mandated academic English proficiency data on all English language learners (ELLs) from landmark United States federal education legislation now makes it possible to track these learners' academic progress longitudinally. Using 5 waves of 9th through 12th grade academic English proficiency data from 2004-2008 for a statewide cohort of 9th grade ELLs (n = 3,702), I employed growth modeling to fit a multilevel model for change in academic English proficiency (Singer & Willet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 57 publications
(69 reference statements)
1
27
0
1
Order By: Relevance
“…Researchers have suggested that research on international students should be extended to the experience of international students with low levels of English language skills (Benzie, 2010;Dooey, 2010;Slama, 2012). To date, few studies have examined the experience of international students with conditional admission that requires students enrolled in a full-time EAP program before starting their degree of study in Western Universities.…”
Section: Conditional Acceptance and English Language Proficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have suggested that research on international students should be extended to the experience of international students with low levels of English language skills (Benzie, 2010;Dooey, 2010;Slama, 2012). To date, few studies have examined the experience of international students with conditional admission that requires students enrolled in a full-time EAP program before starting their degree of study in Western Universities.…”
Section: Conditional Acceptance and English Language Proficiencymentioning
confidence: 99%
“…Research addressing international students has comprehensively focused on issues including aspects of cultural adaptation, social adjustment and learning difficulties (Benzie, 2010, Baker & Hawkins, 2006Chalmers & Volet, 1997). These studies have reported that English language proficiency skills of international students are related to their academic achievement in their program (Slama, 2012), social adjustment (Baker & Hawkins, 2006), and cultural integration (Benzie, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have recommended a closer examination of how to train teachers who serve large proportions of ELLs to provide the necessary support so that ELLs can achieve grade-level standards in high school (Samson & Collins, 2012;Slama, 2012). This study contributes to the understandings of how teachers experience changes in instructional practices with the implementation of the CCSS, especially regarding how these shifts pertain to teachers' work with ELLs.…”
Section: Significance Of the Problemmentioning
confidence: 95%
“…A paucity of research exists on the specific skills that teachers need to develop adolescent ELLs' content knowledge (Faltis, Arias, & Ramírez-Marín, 2010), oral language (Samson & Collins, 2012), and academic language (Faltis, Arias, &Ramirez-Marin, 2010;Francis & Vaughn, 2009;Samson & Collins, 2012;Slama, 2012). Researchers have recommended a closer examination of how to train teachers who serve large proportions of ELLs to provide the necessary support so that ELLs can achieve grade-level standards in high school (Samson & Collins, 2012;Slama, 2012).…”
Section: Significance Of the Problemmentioning
confidence: 99%